Schizo-obsessive disorder in a South Asian context: A case report highlighting religious obsessions and psychosis - Yusuf, Rahemeen; Munir, Rabia; Nizami, Asad; Malik, Ifrah; Nizami, Mahadd; Javaid, Syed (Santé mentale au Québec, 2026)
Background The co-occurrence of schizophrenia and obsessive-compulsive disorder has attracted increasing clinical and research attention, yet it is not recognised as a distinct diagnostic entity in current psychiatric classification systems. This overlap is associated with greater symptom severity, increased suicide risk, and poorer treatment outcomes. Despite its clinical relevance, reports from South Asia remain scarce. This case contributes regional data and supports the conceptualisation of a schizo-obsessive subtype, challenging existing nosological boundaries. Case Presentation We report the case of a 29-year-old man with progressive social withdrawal, persecutory beliefs, and second-person auditory hallucinations. Symptoms emerged insidiously following a relational stressor and included religious-themed command hallucinations leading to a suicide attempt. Concurrently, he experienced intrusive, ego-dystonic religious images during prayer, accompanied by compulsive hand-washing and mental neutralising rituals related to blasphemous fears. There was no history of prior psychiatric treatment, substance use, or neurological illness. Mental state examination and structured assessments supported a diagnosis of schizophrenia with co-morbid moderate obsessive-compulsive symptoms. Treatment with olanzapine, followed by escitalopram, resulted in symptomatic improvement. Exposure and response prevention therapy showed sustained benefit in follow-up. Conclusions This case highlights the clinical importance of recognising co-occurring schizophrenia and obsessive-compulsive symptoms, regardless of medication or neurological issues. Prominent religious themes suggest considering cultural and religious contexts, especially in highly religious societies. As a rare detailed report from Pakistan, it provides valuable regional data and indicates schizo-obsessive presentations may be under-recognised in South Asia. Recognising this profile can improve diagnosis, foster culturally sensitive treatments, and encourage further research.